Efficient rotational cooling of a cold beam of barium monofluoride. (1st February 2022) - Courageux, T; Cournol, A; Comparat, D; Viaris de Lesegno, B; Lignier, H
Abstract: The ability to cool and trap a large number of molecules is currently a crucial challenge for the implementation of various applications in fundamental physics and cold chemistry. We here present an optical cooling of the internal degrees of freedom which maximizes the number of molecules in a minimum number of rotational states. Our demonstration is achieved on a supersonic beam of barium monofluoride seeded in argon, a process that leads to a rotational temperature T rot ≈ 12 K. The rotation is then cooled by our optical pumping to approximately T rot ≈ 0.8 K which, compared to the initial rotational distribution, corresponds to an increase of the number of molecules in the lowest rotational state by one order of magnitude. Our method employs two light sources coming from tapered amplifiers. The first source, dedicated to the rotational cooling of molecules occupying the fundamental vibrational level, is optimized thanks to a spectral shaping whose resolution is comparable to the separation of the relevant rotational levels. The second source is used to pump the molecules back to the fundamental vibrational level when they escape from it. This work focuses on the relevant features of these two types of optical pumping.